GROUP GUIDANCE SERVICES USES ASSERTIVE TRAINING TECHNIQUES TO IMPROVE STUDENTS' INTERPERSONAL COMMUNICATION SKILLS - Dwi Putri, Shintia; Marjohan, Marjohan; Firman, Firman; Sukma, Dina (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
This study aims to demonstrate the role of group bimbigan service using assertive training techniques in improving student interpersonal communication skills. This research uses quasi-experimental design. Sampling techniques use probability sampling with simple random samplings. The sample involved twenty students at the 3rd Basung State High School, Indonesia, divided equally into experimental and control groups. Instruments used to measure interpersonal communication skills are instruments created by researchers and already through judges hired by several experts. Data analysis methods using the wilcoxon signed rank test and kolmogrov smirnov. Results show that group mentoring services use effective assertive training techniques to enhance student interpersonal communication skills. The interpersonal communication skills of the experimental group students before being given group counselling services using assertive training techniques were on average 67.2 then after being given the group coaching services using the asserative training techniques there occurred an improvement on average to 123. Then the control group before being granted the group counseling services was on average 87.1 after having been granted group mentoring services increased on average 105.6. The exhibition showed that group guidance using assertive training techniques can improve student interpersonal communication skills.